Comparing STEM and contextual approaches' impact on students' motivation and learning in acid-base materials - Aji, Latief Susila; Zamhari, Muhammad; Saputra, Febri Ilham; Masrukhah, Dewi (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
This study aimed to compare the impact of science, technology, engineering, and mathematics (STEM) and contextual approaches on students' motivations for learning and achievements in chemistry lessons focused on acid-base materials. A quasiexperimental design with a non-equivalent control group was used, and the participants were 66 students of class XI Science students from State Senior High School 1 (SMA N 1) Kalibawang. Data collection instruments included pre and post-questionnaires and test questions. The findings revealed significant differences in students' learning motivations and achievements between the STEM and contextual approaches to acid-base materials. Both approaches improved students' learning motivations, with the STEM approach yielding higher gains.